Preoperative atorvastatin treatment in CABG patients rapidly improves vein graft redox state by inhibition of Rac1 and NADPH-oxidase activity. - Antoniades, C; Bakogiannis, C; Tousoulis, D; Reilly, S; Zhang, M; Paschalis, A; Antonopoulos, A; Demosthenous, M; Miliou, A; Psarros, C; Marinou, K; Sfyras, N; et al. (2010)
BACKGROUND: Statins improve clinical outcome of patients with atherosclerosis, but their perioperative role in patients undergoing coronary artery bypass grafting (CABG) is unclear. We hypothesized that short-term treatment with atorvastatin before CABG would improve the redox state in saphenous vein grafts (SVGs), independently of low-density lipoprotein cholesterol (LDL)-lowering. METHODS AND RESULTS: In a randomized, double-blind controlled trial, 42 statin-naïve patients undergoing elective CABG received atorvastatin 40 mg/d or placebo for 3 days before surgery. Circulating inflammatory markers and malondialdehyde (MDA) were measured before and after treatment. SVG segments were used to determine vascular superoxide (O(2)(*-)) and Rac1 activation. For ex vivo studies, SVG segments from 24 patients were incubated for 6 hours with atorvastatin 0, 5, or 50 μmol/L. Oral atorvastatin reduced vascular basal and NADPH-stimulated O(2)(*-) in SVGs (P<0.05 for all versus placebo) and reduced plasma MDA (P<0.05), independently of LDL-lowering and of changes in inflammatory markers. In SVGs exposed to atorvastatin ex vivo, without exposure to LDL, basal and NADPH-stimulated O(2)(·-) were significantly reduced (P<0.01 for both concentrations versus 0 μmol/L) in association with a striking reduction in Rac1 activation and 1 membrane-bound Rac1 and p67(phox) subunit. The antioxidant effects of atorvastatin were reversed by mevalonate, implying a dependence on vascular HMG-CoA reductase inhibition. CONCLUSIONS: Short-term treatment with atorvastatin 40 mg/d before CABG improves redox state in SVGs, by inhibiting vascular Rac1-mediated activation of NADPH-oxidase. These novel findings suggest that statin therapy should be maintained or initiated in patients undergoing CABG, independently of LDL levels. Clinical Trial Registration-URL: http://www.clinicaltrials.gov. Unique identifier: NCT01013103.